Autophagy is a new protective mechanism against the cytotoxicity of platinum nanoparticles in human trophoblasts - Nakashima, Akitoshi (Sci Rep, 2019)
Nanoparticles are widely used in commodities, and pregnant women are inevitably exposed to these particles. The placenta protects the growing fetus from foreign or toxic materials, and provides energy and oxygen. Here we report that autophagy, a cellular mechanism to maintain homeostasis, engulfs platinum nanoparticles (nPt) to reduce their cytotoxicity in trophoblasts. Autophagy was activated by nPt in extravillous trophoblast (EVT) cell lines, and EVT functions, such as invasion and vascular remodeling, and proliferation were inhibited by nPt. These inhibitory effects by nPt were augmented in autophagy-deficient cells. Regarding the dynamic state of nPt, analysis using ICP-MS demonstrated a higher accumulation of nPt in the autophagosome-rich than the cytoplasmic fraction in autophagy-normal cells. Meanwhile, there were more nPt in the nuclei of autophagy-deficient cells, resulting in greater DNA damage at a lower concentration of nPt. Thus, we found a new protective mechanism against the cytotoxicity of nPt in human trophoblasts.